Remoção, tratamento e valoração de escuma proveniente de reatores UASB aplicados ao tratamento de esgoto doméstico - Aracele Vieira Santos (2014)
The research aimed to evaluate scenarios for managing the scum from UASB reactors treating domestic sewage. In the first scenario, the effect of the commercial enzymes Lipolase 100L and crude papain on the anaerobic biodegradability of scum was evaluated, with a view to increasing methane production. Preliminary tests were performed in which the scum was subjected to hydrolysis for 24 hours, using different enzyme concentrations (0, 0.10, 0.25, 0.50, 0.75, 1.0 and 5.0% m/v), with the monitoring of acids production. Once the most effective concentration of enzyme was identified, the scum was submitted to anaerobic biodegradation tests. The experimental conditions for the tests were based on UASB reactor operating conditions (30 °C, pH 7.0). The results of the kinetics of hydrolysis showed that the concentration of 1% (w/v) produced more acids for both commercial enzymes. Furthermore, it was found that the crude papain presented a superior performance than the lipase Lipolase 100L in the anaerobic biodegradation of the scum, as confirmed by higher methane production, with a mean value of 950 ml and 720 ml, and higher COD removal efficiencies (79 and 72%) and O&G (80 to 63%), respectively. In the second scenario, we sought to establish a scum disposal protocol in a hydrostatic removal device, in order to enable control of the accumulation of material within TPS (three-phase separators) of a UASB reactor operating at full scale. Additionally, the effectiveness of a screening system and scum dehydration with a view to reducing disposal costs and increasing the energy recovery potential of the scum was evaluated. The results showed that a frequency of two weekly discharges resulted in effective control of scum accumulation in the TPS, as confirmed by the substantial reduction in the volume of scum after the removal operation (only 10-40% of remaining material). In addition, the sieving and dehydration system of scum enabled the effective separation of the coarse fraction and a high efficiency of the drying bed with a volume reduction of about 80%, in just 60 hours of dehydration. The data also showed that the scum retained by the sieve had a greater energy potential than the dry scum retained in the drying bed, of 7.1 and 5.8 MJ.d-1, respectively. These results allow confer important benefits in terms of reducing disposal costs of the scum, as well as raising the energy recovery potential of the sewage treatment plant, in view of its favorable characteristics for use in thermal processes of energy generation.